Peregrine falcon egg pollutants: Mirror Stockholm POPs list including methylmercury. Issue 8 (13th September 2016) - Schwarz, Simon; Rackstraw, Anthony; Behnisch, Peter A.; Brouwer, Abraham; Köhler, Heinz-R.; Kotz, Alexander; Kuballa, Thomas; Malisch, Rainer; Neugebauer, Frank; Schilling, Friedrich; Schmidt, Daniel; Theo von der Trenck, K.
ABSTRACT: The role of the peregrine falcon ( Falco peregrinus ) as a bioindicator for the accumulation of organohalogen compounds and other persistent organic pollutants has been established in field studies. Biometric indices for damage caused by pollutants such as the shell thickness and the shell index were determined and the egg contents were analyzed for various pollutants by gas chromatography/mass spectrometry. A wide range of chemically activated luciferase expression (CALUX®) bioassays were performed on subsamples of the eggs. The following organohalogen compounds were found in the eggs of 2009: dichlorodiphenyltrichloroethane (DDT) and dichlorodiphenyldichloroethane, heptachlor epoxide, hexachlorobenzene, dieldrin, hexachlorocyclohexane, polychlorobiphenyls and polychlorodibenzodioxins and polychlorodibenzofurans, polybromodiphenyl ethers, hexabromocyclododecane, tetrabromobisphenyl A, perfluoro compounds, and mercury. The DDT metabolite, dichlorodiphenyldichloroethene (DDE) (11, 800 ng/g dry matter), was found to be the most highly concentrated egg contaminant followed by 2, 2′, 4, 4′, 5, 5′-hexachlorobiphenyl (3800 ng/g). After a past general drop in pollution level, most egg contaminants presently plateau at levels that may still exceed limit values in foods of animal origin (DDE) or even toxicological thresholds (polychlorobiphenyls + polychlorodibenzodioxins, polybromodiphenyl ethers, perfluorooctanesulfonate, methylmercury). Accumulation of DDE could be shown in peregrine falcon eggs from the uplands of Southwest Germany with elevations up to 1500 m, presumably due to its global distribution and its cold condensation in higher altitudes. In contrast, the concentration of polychlorobiphenyls in falcon eggs decreases with elevation, indicating that these pollutants originate mainly from conurbations and local industrial sites. Significant negative correlations were found between both shell index and thickness and the concentration of Hg. A deleterious effect is also evident from a no-observed-adverse-effect level of 120 ng MeHg per gram egg determined by other authors in chronic feeding studies with ibises, which resulted in decreased egg productivity and male homosexual nesting and courtship behavior. The average Hg concentration in the peregrine falcon eggs from 2009 is almost four times higher than this level. MeHg accounted for 82.5% of the Hg present in the eggs of 2009 and 2010. The cell test DR CALUX® for screening of dioxin-like activities can be used to detect not only the 29 regulated dioxin-like substances but also many other persistent organic pollutants with dioxin-like potencies, such as mixed halogenated dioxins/biphenyls. In our case, the results of bioanalytical screening methods showed no additional effect of other compounds with dioxin-like activity. Ninety-three out of 177 analytes sought could be detected in the eggs. Chlorinated paraffins, organotin compounds, some pesticides that are still in use, and phthalic esters with the exception of traces of diethylhexyl phthalate could be excluded. All pollutants found in the eggs belong to substance classes banned by the Stockholm and Minamata Conventions.